Cost Benefit Analysis for safety projects at sea – Does the method give the entire picture? Experience from analysis of the Stad sea tunnel - Tørset, Trude; Meland, Selveig (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
The method used for CBA of safety projects at sea should be altered to include direct and indirect costs related to precautions taken to avoid risk. This is one of the conclusions from a cost benefit analysis regarding a ship tunnel at Stad, carried out in 2007. Stad is a peninsula located on the western coast of Norway. A tunnel here would give seafarers the opportunity to pass by Stad regardless of the weather conditions and ship size. The waters surrounding Stad are difficult, and this stretch of sea is one of the most feared along the entire Norwegian coast. Interviews and two open meetings gave information about how the people and companies react to the current sailing conditions. Information gathered indicates that aspects of great importance to some of the stakeholders, are not captured by the prevailing CBA method. Today, the seafarers take precautions which would not be necessary if a tunnel was built. This represents costs today and savings should the tunnel be built, and thus the savings should be included in the assessment of the tunnel. Research should be carried out to go more thoroughly into the effects, and the method to assess safety projects at sea. New assessments for sea projects should be altered to take these effects into account.